Analysis of Notary's Legal Remedies for Sanctions of Temporary Dismissal in PTUN Decisions (Case Study of Jakarta Administrative Court Decision No. 88/G/2017/PTUN-JKT) - Tixatmojo, Muhammad Annam Arroffi; Subekti; Itok Dwi Kurniawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The present study conducts an analysis of Notary's legal remedies for temporary dismissal sanctions, legal protection and legal certainty with regard to Notary's legal remedies. This is achieved by means of a case study of the Jakarta State Administrative Court Decision Number 88/G/2017/PTUN-JKT. The objective of this study is to evaluate the Notary's legal remedies for temporary dismissal sanctions and to analyse whether the PTUN Decision has provided legal certainty and legal protection for Notaries. Utilising a normative juridical approach and descriptive analysis method, this research is underpinned by primary data, including Law No. 51/2009 on State Administrative Courts, Law No. 2/2014 on Notary Position, Minister of Law and Human Rights Regulation No. 15/2020, and court decisions. The consequence of this state of affairs is that, in this particular instance, the Notary is entitled to initiate legal proceedings in the State Administrative Court to challenge the sanction of temporary dismissal imposed by the Notary Supervisory Panel. In the course of his legal efforts, the Notary is not accorded legal protection or legal certainty due to disparities in interpretation from the Panel of Judges. This research study lends further credence to the notion that notaries are instrumental in comprehending the self-defense procedures that are enshrined within the internal supervisory system of the Supervisory Council. It is imperative for judges of the PTUN to exercise greater discernment when assessing the characteristics of the decision rendered by the Central Supervisory Council.